Archaeal and methanogenic communities in the rice field under different fertilizer applications - Yuli Fatma; IMAN RUSMANA; ARIS TRI WAHYUDI; HAMIM (Society for Indonesian Biodiversity, 2019)
Abstract. Fatma YS, Rusmana I, Wahyudi AT, Hamim. 2019. Archaeal and methanogenic communities in the rice field under different fertilizer applications. Biodiversitas 20: 3667-3675. The archaeal community in the soil surrounding rice roots plays key roles in biogeochemical cycles. Methanogenic archaea contribute to CH4 production in the rice field and control CH4 emission rates; an important greenhouse gas significantly emitted from the rice field. Characteristic of archaeal and methanogenic community in Indonesian rice field has not been well documented. In this study, rice plants grown in the rice field were treated with two different fertilizer applications, i.e., 100% urea without biofertilizer (250 kg ha-1) (B0), and 50% urea (125 kg ha-1) with biofertilizer consisted of methanotrophic bacteria and N2O-reducing bacteria (B1). Soil archaeal community of the two types of fertilization was characterized over the rice-growing period using 16S rRNA amplicon sequencing. The succession and dynamic of the archaeal population were detected in each of the two treatments before fertilizer application (0 days after transplanting [DAT]) until the rice generative phase (69 DAT). During the period, the archaeal soil community in both treatments was dominated by Crenarchaeota. The relative abundance of putative methanogens was higher in the B0 treatment than that of B1 treatment. Within the methanogenic community, Methanosarcinaceae and Methanomassiliicoccaceae which found as most dominant group in both treatments were presumably to be important contributors to CH4 emission. The application of 50% urea with biofertilizer (B1) changed the structure of the archaeal and methanogenic community in the rice field compared to the application of 100% urea (B0).